A homodyne detector integrated onto a photonic chip for measuring quantum states and generating random numbers. (7th February 2018) - Raffaelli, Francesco; Ferranti, Giacomo; Mahler, Dylan H; Sibson, Philip; Kennard, Jake E; Santamato, Alberto; Sinclair, Gary; Bonneau, Damien; Thompson, Mark G; Matthews, Jonathan C F
Abstract: Optical homodyne detection has found use as a characterisation tool in a range of quantum technologies. So far implementations have been limited to bulk optics. Here we present the optical integration of a homodyne detector onto a silicon photonics chip. The resulting device operates at high speed, up 150 MHz, it is compact and it operates with low noise, quantified with 11 dB clearance between shot noise and electronic noise. We perform on-chip quantum tomography of coherent states with the detector and show that it meets the requirements for characterising more general quantum states of light. We also show that the detector is able to produce quantum random numbers at a rate of 1.2 Gbps, by measuring the vacuum state of the electromagnetic field and applying off-line post processing. The produced random numbers pass all the statistical tests provided by the NIST test suite.